(3GdMLR Ydi GdSajfIs - (3eMeO YHO GdaJGM(B, (3JQcs ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2005)
(3GdMLR GdJMaVj Ydi GdSajfI, GdMLR GdJfajOj Ydi GdSajfIs
(3GdeQGLY U(B.152s
Keywords: (3GdbGfhf GdHMQjs; (3MLR GdeeJdcGJs